Rekonstruksi Konsep Dasar, Pembinaan, dan Pembaharuan Kurikulum dalam Perspektif Pendidikan Kontemporer - Kurnia Alex; Fitriani Muh. Amin; Dadang Sumarna (FKIP UNSULTRA, 2026)
This research aims to reconstruct the basic concepts, development, and renewal of the curriculum from a contemporary educational perspective through a literature study approach. Social change, technological developments, and the demands of globalization are driving the education system to continuously adapt the curriculum to meet the needs of 21st-century students. This study employed qualitative methods with a literature review approach, drawing on various recent scientific sources, such as national and international journals, academic books, and educational policy documents. The results indicate that the basic concept of the curriculum has shifted from a content-oriented approach to a competency- and character-based approach. Furthermore, curriculum development is no longer solely top-down but involves the active role of teachers as curriculum developers at the educational unit level. Curriculum renewal also emphasizes flexibility, learning differentiation, and the integration of digital technology into the learning process. Other findings indicate that the success of curriculum renewal is greatly influenced by teacher readiness, policy support, and the local socio-cultural context. Thus, curriculum reconstruction from a contemporary educational perspective requires a synergy between innovation, adaptation, and sustainability to create an education system that is responsive and relevant to the challenges of the times.